Neutrophil-to-high-density-lipoprotein-cholesterol ratio and mortality among patients with hepatocellular carcinoma - Shi, Ke; Hou, Jie; Zhang, Qun; Bi, Yufei; Zeng, Xuanwei; Wang, Xianbo (Frontiers in Nutrition, 2023)
Background Inflammatory responses and lipid metabolism disorders contribute to the development and prognosis of hepatocellular carcinoma (HCC). This study aimed to investigate the prognostic value of lipid-related inflammatory parameters in patients with HCC. Methods From January 2010 to June 2017, we enrolled 1,639 patients with HCC at Beijing Ditan Hospital. Multivariate Cox regression analysis and area under the receiver operating characteristic (AUC) analysis were used to evaluate and compare the predictability and reliability of high-density lipoprotein cholesterol (HDL-C), neutrophil-to-HDL-C ratio (NHR), monocyte-to-HDL-C ratio (MHR), and lymphocyte-to-HDL-C ratio (LHR) values. A restricted cubic spline was used to explore the association between the NHR and 3-year mortality in patients with HCC. Differences in survival rates were estimated using the Kaplan–Meier method and compared using the log-rank test. The results were validated in an internal cohort between July 2017 and October 2019 (n = 373). Results After adjusting for confounding variables, NHR was independently associated with 3-year mortality, both as a continuous and categorical variable (both p < 0.05). The correlation between the mortality and the MHR and LHR was not statistically significant. The NHR showed a suitable prognostic value (AUC at 3 years: 0.740), similar to that of the Model for End-stage Liver Disease (MELD) (AUC at 3 years: 0.761). In the validation cohort, the AUC of the NHR was 0.734 at 3 years. The optimal cut-off values of NHR and MELD were 3.5 and 9, respectively. The 3-year survival rates in the low- (NHR < 3.5 and MELD <9) and high-risk (NHR ≥ 3.5 and MELD ≥9) groups were 81.8 and 19.4%, respectively, in the training cohort, and 84.6 and 27.5%, respectively, in the validation cohort. Conclusion Baseline NHR is a promising prognostic parameter for mortality in patients with HCC and patients with NHR ≥ 3.5 and MELD ≥9 have a high mortality rate.